Optimal power flow solutions for power system operations using moth-flame optimization algorithm - Alabd, Salman; Mohd Herwan, Sulaiman; Muhammad Ikram, Mohd Rashid (Springer Singapore, 2020)
This article proposes a recent novel metaheuristic optimization technique: Moth-Flame Optimizer (MFO) to solve one of the most important problems in the power system namely Optimal power flow (OPF). Three objective functions will be solved simultaneously: minimizing fuel cost, transmission loss, and voltage deviation minimization using a weighted factor. To show the effectiveness of proposed MFO in solving the mentioned problem, the IEEE 30-bus test system will be used. Then the obtained result from the MFO algorithm is compared with other selected well-known algorithms. The comparison proves that MFO gives better results compared to the other compared algorithms. MFO gives a reduction of 14.50% compared to 13.38 and 14.15% for artificial bee colony (ABC) and Improved Grey Wolf Optimizer (IGWO) respectively